The half known life : in search of paradise - Iyer, Pico (New York : Riverhead Books, 2023)
"A journey through competing ideas of paradise to see how we can live more peacefully in an ever more divided and distracted world"--
Keywords: Spiritual life; Travel -- Religious aspects; Paradise